Lipid Transport in the Human Newborn: PALMITATE AND GLYCEROL TURNOVER AND THE CONTRIBUTION OF GLYCEROL TO NEONATAL HEPATIC GLUCOSE OUTPUT - Bougnères, P. F. (1982)
Free fatty acid (FFA) transport was measured in 11 and glycerol turnover in 5 newborns with continuous tracer infusion of [1-(13)C]palmitate or [2-(13)C]glycerol, respectively. In addition, simultaneous determination of glucose production in the latter group with [6,6-(2)H(2)]glucose tracer and measurement of the appearance rate of [(13)C]glucose derived from [(13)C]glycerol allowed calculation of gluconeogenesis from glycerol. The average FFA inflow rate was 11.5±1.7 μmol kg(−1)min(−1), 2.5-4.5 h after the last feeding, and 16.7±2.8 μmol kg(−1)min(−1), 5-12 h after the last meal. These rates are comparable to those found in adults only after 8-16 h and ∼72 h of fasting, respectively. FFA inflow in the newborn was directly correlated with time of fasting, plasma FFA level, and plasma glycerol level. Palmitate clearance and fractional removal were inversely related to palmitate level. Glycerol flux averaged 4.4±0.5 μmol kg(−1)min(−1), a value three- to fourfold that of the postabsorptive adult. Approximately 75% of transported glycerol was converted to glucose and represented 5.0±0.6% of hepatic glucose production. Furthermore, there was a direct relationship between glycerol turnover and the fraction of glucose coming from glycerol. Despite the absolutely elevated neonatal FFA and glycerol transport rates, these were quantitatively similar to values found in adults with comparable elevated substrate levels. Furthermore, other similarities with the adult in the relationships between inflow transport and substrate values, and between transport and fractional removal suggest that the regulatory aspects of lipid transport in man are already well developed by the first day of life.